2021
DOI: 10.1182/blood.2020009417
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated PD-L1 delays human neutrophil apoptosis and promotes lung injury in an experimental mouse model of sepsis

Abstract: PD-L1 is a ligand for PD-1 and its expression has been shown to be upregulated in neutrophils harvested from septic patients. However, the effect of PD-L1 on neutrophil survival and sepsis-induced lung injury remains largely unknown. Here we show PD-L1 expression negatively correlates with rates of apoptosis in human neutrophils harvested from patients with sepsis. Using co-immunoprecipitation assays on control neutrophils challenged with IFN-γ and LPS, we show PD-L1 complexes with the p85 subunit of PI3-K to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 21 publications
4
68
2
2
Order By: Relevance
“…PD-L1, HLA-DR and CD64 are upregulated in neutrophils exposed to IFN-γ, consistent with our transcriptomic signature data 28–34. The IL-8 receptor CXCR1 was downregulated, potentially reflecting agonist-mediated internalisation of this G protein-coupled receptor.…”
Section: Resultssupporting
confidence: 87%
“…PD-L1, HLA-DR and CD64 are upregulated in neutrophils exposed to IFN-γ, consistent with our transcriptomic signature data 28–34. The IL-8 receptor CXCR1 was downregulated, potentially reflecting agonist-mediated internalisation of this G protein-coupled receptor.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, as compared with classical neutrophils and PMN-MSDCs, N2 TAN produce higher levels of chemokines but lower granules and ROS [ 75 , 76 ]. PD-L1-expressing neutrophils have been identified in cancer, infections, autoimmunity, and sepsis [ 77 , 78 , 79 , 80 , 81 ] and appear to be less prone to apoptosis than their PDL-1-negative counterparts [ 81 ]. Interestingly, these PDL-1-expressing neutrophils suppress the immune response by limiting activity of PD-1-expressing cells [ 77 , 78 , 79 , 80 , 81 ], culminating in either a protective or deleterious role according to the pathological context.…”
Section: Neutrophils: From Phagocytosis Sentinel To Immunoregulation ...mentioning
confidence: 99%
“…A study has shown that inhibiting the CDK4/6 pathway can inhibit the NET production pathway and cause apoptosis [ 19 ]. The inhibition of AKT prevented NETs production and instead switched to caspase-dependent apoptotic pathways [ 37 ]. AKT is associated with several proteins related to cell survival, including GSK-3β, P21, and P27 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%